Multifocal and Microvascular Involvement in Ischemic Stroke During COVID-19: A Cohort Study With Comparison With Non-COVID-19 Stroke - Hautecloque, Geoffroy; Kempf, Christian; Stan, Camélia; Arentz-Dugay, Marie-Hélène; Vuillemet, Francis; Ahle, Guido; Sellal, François; Martinot, Martin (Frontiers in Neurology, 2021)
Introduction: Thromboembolic events, including ischemic stroke, are major complications of coronavirus disease 2019 (COVID-19). The clinical characteristics of COVID-19-related stroke are not clearly defined, and few controlled studies assessed the underlying mechanisms of cerebrovascular complications of COVID-19. This single-center retrospective observational study compared stroke characteristics between patients with and without COVID-19. Methods: This study included all patients hospitalized between March 1, 2020, and April 30, 2020, in Colmar Hospital for ischemic stroke as confirmed by imaging. The characteristics of patients with laboratory-confirmed severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection by real-time reverse transcriptase polymerase chain reaction or serology were compared with those without SARS-CoV-2 infection. Result: Among 772 patients, nine COVID-19 patients were compared with 50 patients without COVID-19. The following inflammatory and procoagulant marker levels were significantly higher in the COVID-19 group than those in the control group: C-reactive protein, 57.3 ± 43.4 vs. 15.0 ± 30.6 mg/L, p < 0.001; fibrinogen, 5.89 ± 1.75 vs. 4.03 ± 1.26 g/L, p < 0.001; and D-dimer, 4,833.9 ± 6,549.4 vs. 1,028.6 ± 942.6 ng/ml, p < 0.001. The rates of multifocal cerebral territory involvement (4 vs. 7, p = 0.05), microvascular involvement (4 vs. 6, p = 0.04), and thrombophilia (4 vs. 4, p = 0.014) were significantly higher in the COVID-19 group than in the control group, whereas no significant intergroup differences were found in the stroke mechanisms, i.e., cardio-embolic, atherosclerotic, small vessel disease, and cryptogenic. Conclusion: COVID-19-related stroke is characterized by hypercoagulability and hyperinflammation that may favor strokes via microvascular circulation abnormalities, microthrombus formation, and multifocal lesions.